Analysis of the psoralen-crosslinking pattern in chromatin DNA by exonuclease digestion. - Widmer, R M (1988)
When chromatin is photoreacted with psoralen, crosslinks occur preferentially in the linker DNA between nucleosomes. The pattern of these crosslinks can be analysed by exonuclease digestion of random DNA fragments, since the exonucleases tested stop at sites of psoralen-crosslinks. Further digestion of these fragments with S1-nuclease leads to DNA fragments of nucleosomal and polynucleosomal size, which presumably carry psoralen-crosslinks at both ends. This method of analysis of chromatin structure complements the classical micrococcal nuclease digestion analysis, since it can be performed in vitro as well as in vivo, and since it is independent of pH and ionic conditions.